Military-Industrial aspects of Turkish defence policy - Wiśniewski, Rafał (Rocznik Integracji Europejskiej, 2015)
This paper aims to analyse the military-industrial aspects of Turkish defence policy. A sophisticated and profitable defence industry is a useful tool for a state’s foreign and security policy. It not only supplies the armed forces with the necessary weapons and military equipment, but can also bring political influence on the international arena through arms transfers and military-industrial cooperation. These realities are not lost on Turkish decision makers. That is why they have made the nurturing of an indigenous defence-industrial base a distinct state policy. In this paper, the defence industry’s functions in the framework of Turkish defence and security policy are defined, the condition and structure of Turkish defence and aerospace sector is analysed and conclusions regarding its future prospects are presented. This provides the basis for a wider analysis of the defence-industrial aspects of Turkish defence and security policy.